Evaluasi Penerimaan ChatGPT oleh Mahasiswa dalam Mendukung Perkuliahan Di Surabaya - Han Familiya; Pratama, Arista; Faroqi, Asif (E-Jurnal Universitas Samudra, 2025)
Information technology, especially the internet, is developing rapidly. According to We Are Social, internet users in Indonesia will increase in January 2023 compared to the previous year. Artificial Intelligence (AI) such as ChatGPT, makes human work easier and is frequently utilized in many sectors, including education. Surabaya is the city with the most universities in East Java, having 74 universities. However, ChatGPT has limitations in information accuracy and understanding complex contexts. The focus of this research is to identify factors that influence the acceptance of ChatGPT with modified TAM by students at universities and state educational institutions in Surabaya. With 399 respondents, the test used the SEM-PLS technique and SmartPLS 3 software. The research results showed that the intrinsic motivation (IM) variable had a significant effect on ease of use (PEOU). The variables intrinsic motivation (IM) and perceived usefulness (PU) have a positive and significant effect on behavioral intention (BI) in using ChatGPT. Apart from that, the variables ease of use (PEOU) and intrinsic motivation (IM) also have a positive and significant influence on perceived usefulness (PU). Meanwhile, the ease of use (PEOU) variable on behavioral intention (BI) has a positive but not significant influence. Perceived ease of use (PEOU) of ChatGPT does not directly influence users' desire to use (BI) ChatGPT through the intermediary of perceived usefulness (PU).